Let's review Izzie's steps and see if she made any mistakes while solving the inequality.
The original inequality is: \[ 3(t+1) - 4t \geq -5 \]
Step 1
Distributing the 3: \[ 3t + 3 - 4t \geq -5 \]
This step is correct.
Step 2
Combining like terms: \[ -t + 3 \geq -5 \]
This step is also correct.
Step 3
Now, to isolate \( t \), Izzie subtracts 3 from both sides: \[ -t \geq -5 - 3 \] \[ -t \geq -8 \]
This means Izzie's Step 3 is incorrect. Instead of \( -2 \), she should have \( -8 \).
Step 4
In this step, when she multiplied both sides by -1, she incorrectly changed the direction of the inequality: From: \[ -t \geq -8 \] to: \[ t \leq 8 \]
This step directly matches the correct inequality conclusion.
To summarize:
- Izzie made a mistake from Step 2 to Step 3 where she combined the numbers incorrectly.
- The final answer after fixing the steps should lead to \( t \leq 8 \) which Izzie did arrive at, but she had an error in the process.
Conclusion:
The correct evaluation is Izzie made a mistake going from step 2 to step 3.